Meryl Streepová a Emma Stone: The inflection of foreign surnames in Czech through the prism of the corpus research - David, Jaroslav; Místecký, Michal (Bohemistyka, 2023)
The goal of the study is to seek for mechanisms that determine creation of female forms of foreign surnames in Czech in the material from the Czech National Corpus SYN, version 9. To this end, we investigate the corpus frequencies of the names of European female presidents and prime ministers who were active in the 2010–2019 timespan, and of the names of actresses who received the Academy Award for Best Actress (the Oscar) in the same period. On the grounds of statistical testing, the paper finds out if profession, age, or declension of the first name play a role in whether surname feminization takes place. Besides the results, the research hints at the fact that there are many factors at play, for example, name length, spelling difficulties, or the mechanism of “syntactic attraction”.